Effects of mutation helix termini on stability and activity of Geobacillus SP. strain arm lipase - Zakariya @ Zainuddin, Norhayati (2013)
A thermophilic Geobacillus sp. strain ARM was found to produce a thermostable lipase. The Geobacillus sp. strain ARM lipase amino acid sequence was used to predict its corresponding three dimensional structure thus providing the means for protein engineering. The common characteristics of the mutated Geobacillus sp. strain ARM lipases were studied and compared to the recombinant wild type enzyme to determine the new properties developed upon mutation. More than 20 years ago, dipole moment was studied towards the stability of protein but the correlation between dipole moment and protein is not fully understood. Rational design was used to create mutations at helix termini based on the dipole moment theory. The two point mutations were predicted by computer modeling to investigate the relationship between dipole and protein stability. Subsequently, the thermostable Geobacillus sp. strain ARM lipase and its variants were subjected to molecular dynamic simulations in order to analyze their structural conformation with regards to stability,flexibility and the interaction between amino acid residues within the structure. Experimental studies were carried out to validate the in silico studies. The lipase variants showed a marked difference from the wild-type in the interaction of residues within the protein interior and exterior with slight changes in the stability and flexibility. The overall stability of the modeled Geobacillus sp. strain ARM lipase was altered by the mutations and different dynamical behaviour was observed in the molecular dynamic simulations. The recombinant Geobacillus sp. strain ARM lipase and the A79D lipase variant were found to function optimally at 60°C, whislt, the S236R lipase was found to hydrolyze the substrate actively at 55°C. In spite of the reduced activity of both variant lipases,substitution of serine to arginine decreased the thermostability of the S236R lipase to 45°C as opposed to 50°C for the wild-type Geobacillus sp. strain ARM and the A79D lipase during 30 min of incubation time. In contrary, the half-life of S236R lipase was 4 h, the same as the half-life of Geobacillus sp. strain ARM lipase whereas the A79D lipase has a half life of only 2 h. The optimum pH for activity of the variants also shifted one unit where the optimal pH for both variants, A79D and S236R were at pH 9 instead of 8 (wild-type), whereas for the wild-type Geobacillus sp. strain ARM lipase and both the variant lipases maintained their pH stability within the range of 6 to 9. Meanwhile, the mutations showed no effects in activity using different natural oils as a substrate. A residue substitution at the helix terminal did cause dynamical changes in the structural conformation due to position of both mutated amino acid located at the surface of the enzyme. Thus, it is suggested the replacement of one amino acid can contribute in altering the structure stability, flexibility and re-arrangement.